Low etiologic fraction for human papillomavirus in larynx squamous cell carcinoma. (October 2016) - Taberna, M.; Resteghini, C.; Swanson, B.; Pickard, R.K.L.; Jiang, B.; Xiao, W.; Mena, M.; Kreinbrink, P.; Chio, E.; Gillison, M.L.
Highlights: A single institutional case-series in the US to estimate the EF for HPV LSCC. The etiological fraction for HPV was less than 2% in LSCC. Low-risk HPV may rarely cause LSCC. p16 IHC should not be used as a surrogate for HPV in LSCC. Abstract: Background: Human Papillomavirus (HPV) is a cause of oropharyngeal squamous cell carcinoma (OPSCC), but its pathogenic role in larynx squamous cell carcinoma (LSCC) remains unclear. Material and methods: A single-institutional, retrospective case-series was performed to estimate the etiological fraction (EF) for HPV in LSCC. Eligible cases included 436 consecutive cases of LSCC diagnosed (2005–2014) at The Ohio State University Medical Center. HPV DNA presence was detected by consensus primer PCR (Inno-LiPa) and HPV type-specific qPCR. HPV E6/E7 mRNA expression was detected by type-specific qRT-PCR. Tumor p16 expression was evaluated by immunohistochemistry (IHC). Results: HPV DNA was detected by Inno-LiPa in 54 of 404 (13.4%, 95% CI 10.2–17.1) evaluable samples but was confirmed by HPV type-specific qPCR in only 14 (3.5%, 95% CI 1.9–5.7). Only 7 of 404 (1.7%, 95% CI 0.7–3.5) LSCC were positive for HPV E6/E7 mRNA expression, including HPV16 (n = 4) and 1 each for 11, 26 and 33. In the HPV11-positive tumor, Sanger sequencing discovered 6 nucleotide mutations in the upstream regulation region, E6 and E7. Of 404 LSCC, 18 had strong and diffuse p16 expression. In comparison to a gold standard of HPV E6/E7 mRNA expression, p16 expression had a sensitivity of 71.4% (95% CI 29.0–96.3), specificity of 96.7% (95% CI 94.5–98.3), positive-predictive-value (PPV) of 27.8% (95% CI 9.7–53.5) and negative-predictive-value of 99.5% (95% CI 98.1–99.9). Conclusion: The EF for HPV in LSCC is low (1.7%) in a geographic region with high EF for OPSCC. Low-risk HPV may rarely cause LSCC. Finally, p16 expression has poor PPV for HPV in LSCC.